Normalizing urban inequality: cinematic imaginaries of difference in postcolonial Amsterdam. (19th May 2017) - van Gent, Wouter; Jaffe, Rivke
Abstract: Combining insights from critical urban studies with geographies of race and racism, this article examines the role of spatial imaginaries in normalizing urban inequalities, showing how such imaginaries make the associations between places and populations appear natural. We extend analyses of the interplay between material landscapes and imaginative geographies to examine how these connections feature in processes of gentrification and displacement and emphasize the necessity of an intersectional approach in understanding the cultural underpinnings of urban change. We propose that such analyses of dominant spatial imaginaries benefit from attention to their colonial roots, given the persistence of monomythical explorer-hero narratives and the mapping of reworked colonial imaginative geographies onto contemporary postcolonial cities. Our analysis focuses on Amsterdam, the popular Dutch film Alleen Maar Nette Mensen and the spatiality of difference that its 'monomyth' narrative presents. It justifies an unequal urban order by contrasting Amsterdam's city centre, which is depicted as White, middle-class and 'civilized', with the post-war urban periphery, which is cast as a mysterious place of racialized poverty, squalor and pathological behaviour. This culturally essentialist depiction contributes to the depoliticization of state-led gentrification and normalizes changes to the material cityscape.